Pengaruh Media Pembelajaran Zoom Meeting Online Terhadap Motivasi Belajar Dan Hasil Belajar Peserta Didik Paket B Pada Mata Pelajaran IPS Di PKBM Homeschooling Kak Seto Surabaya - Sari, Safitri Rosela; Yusuf, Ali (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research aims to explore the influence of the Zoom Meeting Online learning media on the learning motivation and learning outcomes of package B students in social studies subjects at PKBM Homeschooling Kak Seto Surabaya. In the analysis using the SEM SmartPLS 4 For Windows application with 22 samples, a path coefficient value of 0.581 was found for learning motivation and 0.584 for learning outcomes. Data management results show T-Statistics values ??of 3.731 and 4.208 respectively, exceeding the T-Table value with a significance of 0.000. These findings confirm that the use of Zoom Meeting Online has a significant effect on students' learning motivation and learning outcomes. This research provides an important contribution in the context of developing online learning methods, especially in increasing student motivation and learning outcomes in the homeschooling environment. Thus, Zoom Meeting Online is an effective choice in improving the quality of learning in the current digital era, providing the necessary support for alternative educational institutions such as PKBM Homeschooling Kak Seto Surabaya.